Teachers’ perspectives on extra-curricular activities to enhance foundation program language learners’ academic and social performances - Hranush Ginosyan; Victoria Tuzlukova; Timothy Hendrix (Politeknik Negeri Bali, 2019)
Extra-curricular activities have been encouraged to support foundation program students’ positive attitude to learning and their smooth transition into the higher education system with better academic and social performances. This paper discusses the study that explores the potential benefits of foundation program students’ involvement in extracurricular activities from the perspective of teachers who develop, lead and facilitate them at the Centre for Preparatory Studies of Sultan Qaboos University in Oman In particular, the study focuses on how teachers perceive the effects of extracurricular activities on student performance in relation to eight key areas, namely development of students’ language skills and academic performance, development of communicative competency, students’ needs and interests, students’ self-esteem and self-confidence, students’ motivation and positive attitudes towards learning, extracurricular activities in the framework of the foundation program curriculum, cross-cultural experiences, and transitional challenges. The results indicate that extracurricular activities play a valuable role in helping foundation program students adjust to higher education environment and function more easily in English. However, more student involvement and additional assistance to students are needed in order to boost their motivation and increase engagement in their own learning experiences.